Pemanfaatan FMA dan Tanaman Inang untuk Meningkatkan Pertumbuhan Bibit Cendana (Santalum album Linn.) - Magdalena Sunarti Pareira; Irdika Mansur; Dewi Wulandari (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
The sandalwood tree (Santalum album Linn.) is an important tree species as well as a primadonna for the people of East Nusa Tenggara (NTT). It has high economic value for its aromatic wood and essential oil content that have a very distinctive aroma used to make various products such as handicrafts, woodcarvings, incense, and oil for the perfume and cosmetics industry. Sandalwood is a semi parasite plant that part of its life phase requires a host plant to get the nutrients and water. There are many types of host plants that have been used, among others, Casuarina equisetifolia, Acacia mangium, Terminalia microcarpa, Sesbania grandiflora, Alternanthera sp and Capsicum annum. In this research will be tested to try sandalwood planted with Cymbopogon nardus host plants, in terms of economics can provide benefits.Arbuscular mycorrhizal fungi (AMF) is a group of fungi from glomeromycota phylum that can symbiosis mutualism with root system of high level plant. The working principle of the mycorrhiza is to infect the root system of the host plant, producing intensive hyphae tissue so that the plant containing mycorrhiza will be able to increase the capacity in nutrient uptake. The utilization of host plants Alternanthera sp, Capsicum annum, and its application with AMF is the best solution to overcome the problem of developing sandalwood in TTU on the nursery. The purpose of this study was to analyze the effectiveness of AMF and utilization of the atsiri host plant to increase the growth of sandalwood seedlings in TTU. This study was designed using a complete random method (RAL) in split plot design. If the treatment has a significant effect then followed by Duncan Multiple Range Test (DMRT). Parameters observed were height (cm), number of leaf, diameter of sandalwood (mm), dry weight of root, seed quality index, ratio of root buds, and haustorium observation of Sandalwood, and also number of spore, root colonization and AMF dependency of Sandalwood.The results showed that the treatment of AMF with Capsicum annum host plant was 19.8 of high, number of leaf 18.9 on FMA treatment with host plant Capsicum annum, diameter of stem 2.24 mm on Alternanthera sp host treatments without AMF and 1.83 mm at AMF treatment with host plant Capsicum annum, dry weight of buds 2.00g on AMF treatment with Capsicum annum host plant, dry weight of roots AMF (M1) with alternanthera sp 0.70 g, root buds ratio of AMF with host plant alternanthera sp 4.05, seed quality index AMF with Alternanthera sp 4.16 and 82 % of root colonization on AMF with host plant Capsicum annum.Keywords: Santalum album Linn., AMF, host plant.